Migrations, arts, and bodies: the Silhouette in multiple shadows of Rubiane Maia - Guerra, Paula (Frontiers in Sociology, 2025)
This article explores the work of the Brazilian artist Rubiane Maia, currently based in the United Kingdom, focusing on two of her performances as a privileged sociological field for analyzing migration, corporeality, and contemporary art. The main objective of this article is to examine how the artist mobilizes interdisciplinary practices to interrogate memories, displacements, and relations between humans and more-than-humans, focusing on two artistic creations: the Book-Performance and the Speirein. Through a qualitative approach, the analysis highlights how Maia choreographs border experiences, challenging fixed identities and proposing new ways of inhabiting both body and territory. Our study demonstrates how the artist transforms the vulnerability of the migrant body into a creative force, establishing critical dialogues with collective memory and the public sphere.